Fish species composition in the area of Soai Rap estuary, Ho Chi Minh city - Huan, Nguyen Xuan; Nam, Nguyen Thanh; Thanh, Nguyen Nhu (Academia Journal of Biology, 2015)
Soai Rap estuary is the mouth of Dong Nai river, one of the largest rivers in Vietnam. Although, the fish resource in this estuarine area is very important for local people but poorly studied. Based on fish specimens collected in 2 surveys in the field work in the area of Soai Rap estuary from 5 to 11 August, 2011 (in the rainy season) and from 20 to 28 March, 2012 (in the dry season), the total number of 131 fish species belonging to 58 families of 15 orders is recorded. Of those, the order Perciformes is the most dominant, with 74 species (making up 56.49% of total species) in 32 families (55.17% of total families). In fish fauna of Soài Rạp estuary, demersal and benthopelagic fishes constituted a larger proportion in the community compared to pelagics (63.36%, 20.61% and 16.03%, respectively) while the number of brackishwater fish species is equivalent to the number of marine ones (66 species and 65 species, respectively). In the area, there are three species that has been recorded in Vietnam Red Data Book (2007) in the level of Vulnerable species (VU), consiting of Konosirus punctatus, Nematalosa nasus and Tenualosa toli.